2012
DOI: 10.1016/j.cub.2012.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Encoding of Spatial Information during Active Visual Fixation

Abstract: Summary Humans and other species continually perform microscopic eye movements, even when attending to a single point [1-3]. These movements, which include microscopic drifts and microsaccades, are under control of the oculomotor system [2, 4, 5], elicit strong responses throughout the visual system [6-11], and have been thought to serve important functions [12-16]. The influence of these fixational eye movements on the acquisition and neural processing of visual information remains unknown. Here, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
272
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(312 citation statements)
references
References 31 publications
18
272
2
Order By: Relevance
“…The small, ongoing movements of the eye during fixation do not represent a disturbing signal, but rather help the visual system to process fine spatial details. The beneficial role of fixational drift is thought to unfold already during retinal processing by redistributing the temporal frequency power into a range of increased retinal sensitivity (Kuang et al, 2012) and by decorrelating highly redundant input from natural scenes (Rucci and Victor, 2015). Therefore, the view has emerged that fixational drift is adapted to an image to transform visual signals into an optimized spatiotemporal code for further visual processing (Kagan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The small, ongoing movements of the eye during fixation do not represent a disturbing signal, but rather help the visual system to process fine spatial details. The beneficial role of fixational drift is thought to unfold already during retinal processing by redistributing the temporal frequency power into a range of increased retinal sensitivity (Kuang et al, 2012) and by decorrelating highly redundant input from natural scenes (Rucci and Victor, 2015). Therefore, the view has emerged that fixational drift is adapted to an image to transform visual signals into an optimized spatiotemporal code for further visual processing (Kagan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biological systems may exploit a similar strategy. It has been suggested that fixational eye movements play a fundamental role in feature extraction by removing spatial correlations [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to generate sensor motion, we employ a fixation eye movement model based on [15]. The Dynamic Vision Sensor (DVS) is mounted on a pan-tilt head that is actuated by two independent servo motors.…”
Section: Introductionmentioning
confidence: 99%
“…Classic measurements of the TCSF, done with flickering targets set in a dark surround, showed that the luminance TCSF is bandpass with a peak ϳ8 Hz (de Lange, 1958;Kelly, 1961). However, if the surround luminance is changed from dark to the mean-gray of the target modulation, sensitivity to low frequencies increases many-fold, making the TCSF low-pass (Kelly, 1961(Kelly, , 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Kelly (1969Kelly ( , 1971Kelly ( , 1972Kelly ( , 1979 proposed that fixational eye movements introduce highfrequency transients into cellular responses, resulting in lower thresholds on mean-gray surrounds, but not on dark surrounds. The eye movement hypothesis was challenged by experiments with stabilized images that claimed no differences between stabilized and regular viewing conditions, and a lateral inhibitory model was proposed (Keesey, 1970).…”
Section: Introductionmentioning
confidence: 99%